2012
DOI: 10.1017/s1368980012004296
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of breakfast skipping and type of breakfast consumed with overweight/obesity, abdominal obesity, other cardiometabolic risk factors and the metabolic syndrome in young adults. The National Health and Nutrition Examination Survey (NHANES): 1999–2006

Abstract: ObjectiveTo examine the association between breakfast skipping and type of breakfast consumed with overweight/obesity, abdominal obesity, other cardiometabolic risk factors and the metabolic syndrome (MetS).DesignCross-sectional. Three breakfast groups were identified, breakfast skippers (BS), ready-to-eat-cereal (RTEC) consumers and other breakfast (OB) consumers, using a 24 h dietary recall. Risk factors were compared between the breakfast groups using covariate-adjusted statistical procedures.SettingThe 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
158
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(177 citation statements)
references
References 40 publications
14
158
2
3
Order By: Relevance
“…52,57 Conversely, among 415 healthy Korean adults, rare breakfast eaters (eating breakfast 1 of 3 days) were less likely to have elevated serum triglycerides (≥150 mg/dL). 35 Notably, in the Korean study, the percent of TEI from carbohydrates was lower and the percent from fat was higher in rare breakfast eaters, which may explain this observation.…”
Section: Breakfast Skipping and Other Cvd Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…52,57 Conversely, among 415 healthy Korean adults, rare breakfast eaters (eating breakfast 1 of 3 days) were less likely to have elevated serum triglycerides (≥150 mg/dL). 35 Notably, in the Korean study, the percent of TEI from carbohydrates was lower and the percent from fat was higher in rare breakfast eaters, which may explain this observation.…”
Section: Breakfast Skipping and Other Cvd Risk Factorsmentioning
confidence: 99%
“…33,[40][41][42][43][44][45][46][47][48][49][50][51] For example, in NHANES 1999 to 2002, young adults (n=5316; age, 20-39 years) who reported consuming ready-to-eat cereal were 31% less likely to be overweight/obese and 39% less likely to have abdominal obesity compared with breakfast skippers. 52 Additionally, a meta-analysis of 19 studies in the Asian and Pacific regions (n=19 108 participants) demonstrated a pooled odds ratio (OR) of 1.75 (95% confidence interval [CI], 1.57-195) for prevalence of overweight or obesity among the lowest compared with the highest breakfast consumption frequency. 53 The association between breakfast consumption and lower risk of obesity and weight gain is supported further by results from several large, long-term, prospective, observational studies.…”
mentioning
confidence: 99%
“…Behaviours such as low physical activity, high screen time, skipping breakfast and low meal frequency are prevalent in young populations [5,6,7,8,9], and all of them have been linked to an increased risk of childhood obesity and therefore defined as obesogenic behaviours [5,6,10,11,12]. Most studies investigated the individual impact of these behaviours on obesity risk [5,6,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advice promoting regular breakfast consumption to help control body weight [4,5], the number of people skipping breakfast has increased [6,7]. Epidemiological studies report that regular consumption of breakfast, particularly cereal [4,5,6,8,9], is associated with lower BMI and cardiometabolic risk profile [5,6,9,10,11]. Both cross-sectional and prospective studies of breakfast habits and body weight have demonstrated inverse associations between breakfast intake and relative body weight [6,12,13,14].…”
Section: Introductionmentioning
confidence: 99%